2016
DOI: 10.1002/mrd.22747
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking alters sialylation in the Fallopian tube of women, with implications for the pathogenesis of ectopic pregnancy

Abstract: Summary sentence: The expression of sialyltransferases decreases during tubal ectopic pregnancy in women and cigarette smoking alters the expression of ST6GAL1 and ST3GAL5, potentially resulting in a decreased tubal transport and an increased receptivity for blastocysts. AbstractWe recently reported potential involvement of galectin-1 and galectin-3,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The pathogenesis is still not clear. The known risk factors include reduced or impaired tubal transport activity, increased tubal receptivity for blastocyst implantation, tubal damage due to surgery or infection, in vitro fertilization, and cigarette smoking [ 13 , 14 ]. REP is very rare with a total of less than 20 cases reported in the English literature [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis is still not clear. The known risk factors include reduced or impaired tubal transport activity, increased tubal receptivity for blastocyst implantation, tubal damage due to surgery or infection, in vitro fertilization, and cigarette smoking [ 13 , 14 ]. REP is very rare with a total of less than 20 cases reported in the English literature [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar impact could be anticipated in older women, but the age limit of 38 years might have prevented us from observing this phenomenon. Although the interaction between treatment effect of oil-based contrast and smoking was not statistically significant, smokers have tubal damage and dysfunction induced by nicotine and other smoking-related chemicals, which may be related to more tubal debris and mucus plugs caused by abnormal ciliogenesis associated with smoking (Nio-Kobayashi et al , 2016, Shao et al , 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, few evidence demonstrated the pathological roles of sialylation in reproductive diseases. Nio-Kobayashi et al [50] explored that cigarette smoking altered a2,3and a2,6-sialylation in the fallopian tube epithelium, and was potentially a source of decreased tubal transport and with implications for the pathogenesis of ectopic pregnancy. In this study, we found that a2,3-sialylation was increased in RL95-2 cells and mouse uterine endothelium at PD4, which both represent a highly receptive status.…”
Section: Discussionmentioning
confidence: 99%